Relationships among misunderstanding, relationship type, channel, and relational satisfaction. Issue 5 (19th October 2020) - Edwards, Renee; Frost, Jonathon; J.Harvey, Adam; Navarro, Michael; T. Adams, Brock
ABSTRACT: This study examined the relationship between misunderstanding and relational satisfaction, whether friends and romantic partners have different experiences, and the role of channel. Participants ( N = 400) described misunderstandings and responded to scaled items. Relational satisfaction is associated with less frequent misunderstanding and open communication. Misunderstandings between romantic partners are rated more serious than those with friends. Mediated misunderstandings are judged to occur more frequently than face-to-face misunderstandings.